Moral Wounds and Moral Repair: The Dilemmas of Spirituality and Culturally Sensitive Practice. Issue 2 (April 2019) - Sullivan, W. Patrick; Starnino, Vincent R.
As our understanding of trauma is expanding, greater consideration is being given to factors such as moral injury and spirituality. Moral injury appears to be especially pertinent in the case of war-related trauma, as one may not only be the victim of, or witness to, troubling events but also be the perpetrator of acts that run counter to personal values. For some, moral beliefs and values and key elements of the assumptive world are intertwined with spiritual and religious matters. This article discusses moral injury and repair in the context of spiritually and culturally sensitive practice. Strategies for addressing issues such as moral anguish, loss of meaning, identity disturbance, guilt and shame, forgiveness, and spiritual struggle are discussed.